Mathematical model of the thermal-air regime of a ventilated attic - Piotrowski, Jerzy Zbigniew; Stroy, Anatoliy; Olenets, Marianna (Journal of Civil Engineering and Management, 2015)
This paper presents the developed mathematical models that characterize the thermal-air regime of a ventilated attic in the summer and winter seasons. The relevance of the mathematical models was shown and examples of applying these models to solve some engineering problems were presented. Mathematical models can be used to analyze and evaluate changes in the temperature and heat flux (the radiant and convective component) along the air movement in the attic and to select the materials for the roof and floor, as well as for the calculation of ventilation for different climatic conditions.